Malaria control at a gold mine in Sadiola District, Mali, and impact on transmission over 10 years. (1st December 2015) - Wragge, Sue-Ellen; Toure, Dramane; Coetzee, Marelize; Gilbert, Allison; Christian, Riann; Segoea, Godira; Hunt, Richard H.; Coetzee, Maureen
Abstract : Background: The SEMOS gold mine's malaria vector control programme forms part of the company's community responsibilities with the programme being managed by the mine's health department since 2005. Methods: Data from approximately 10 years of malaria vector control for the Sadiola District are given: namely malaria vector control methods used by the control programme, positive malaria case data and entomological surveys from 2006, 2011 and 2014. Results: Distribution of pyrethroid-treated bed nets and indoor residual spraying (IRS) with deltamethrin were implemented by the programme from 2005–2011. No IRS was done in 2012. Spraying with the organophosphate, pirimiphos-methyl resumed in 2013 and 2014 and was followed by a 70% drop in malaria cases in 2014. Anopheles arabiensis was the major vector present in 2006 and was susceptible to deltamethrin. In 2011 and 2014, An. gambiae s.s. was the most abundant vector with deltamethrin 24 h mortality of 68% and 19%, respectively. Conclusions: Resistance to the pyrethroid deltamethrin has increased in An. gambiae s.s. since 2011, possibly due to the scale-up in distribution of long-lasting insecticide-treated bed nets. Resistance management strategies are recommended using different classes of insecticides for IRS, and including the distribution of new-generation bed nets.